2021
DOI: 10.1038/s41598-021-02626-z
|View full text |Cite
|
Sign up to set email alerts
|

Site specific incidence rate of virulence related genes of enteroaggregative Escherichia coli and association with enteric inflammation and growth in children

Abstract: There is a lack of information highlighting the possible association between strain carrying genes of enteroaggregative Escherichia coli (EAEC) and environmental enteric dysfunction (EED) and on linear growth during childhood. Strain carrying genes of EAEC from stool samples collected from 1705 children enrolled in the MAL-ED birth cohort were detected by TaqMan Array Cards. We measured site-specific incidence rate by using Poisson regression models, identified the risk factors and estimated the associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(62 reference statements)
0
11
0
Order By: Relevance
“… 41 A multicountry cohort study, MAL-ED, found that EAEC had an inverse association with linear growth at 24 months of age. 16 The increased prevalence of the aaiC pathogenic variant in our study compared with other EAEC variants may provide more evidence for the plasmid aggregative adherence (pAA’s) gene transfer. Our findings show that aaiC is an incongruent marker for EAEC identification and our findings are consistent with those of research conducted in southern Mozambique.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“… 41 A multicountry cohort study, MAL-ED, found that EAEC had an inverse association with linear growth at 24 months of age. 16 The increased prevalence of the aaiC pathogenic variant in our study compared with other EAEC variants may provide more evidence for the plasmid aggregative adherence (pAA’s) gene transfer. Our findings show that aaiC is an incongruent marker for EAEC identification and our findings are consistent with those of research conducted in southern Mozambique.…”
Section: Discussionmentioning
confidence: 68%
“…However, in the MAL-ED study, the presence of EAEC variants harboring both aaiC and aatA was linked to a higher risk of growth failure in Bangladeshi children. 16 Other studies suggested that the presence of different virulence genes from within and outside the plasmid AA is necessary for complete EAEC virulence. 43 In the case of EAEC, malnutrition and growth impairment may be due to intestinal inflammation or to the thick mucosal gel with which they are associated in human intestinal explants, which could theoretically impair absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Concurrent reports from studies carried out in the settings of the MAL-ED study have shown that asymptomatic infection by diarrheal enteropathogens such as Campylobacter jejuni/coli, EAEC, enterotoxigenic Bacteroides fragilis contribute to enteric inflammation. [5][6][7] Upper gastrointestinal (GI) endoscopy is widely regarded as the gold standard for the diagnosis of EED. 8 Although a few studies have used upper GI endoscopy to study the pathophysiology of EED, 9,10 the invasive nature of the procedure and the requirement of specialized clinical settings and expertise renders it infeasible to be carried out among children in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Concurrent reports from studies carried out in the settings of the MAL-ED study have shown that asymptomatic infection by diarrheal enteropathogens such as Campylobacter jejuni/coli , EAEC, enterotoxigenic Bacteroides fragilis contribute to enteric inflammation. 5 7 …”
Section: Introductionmentioning
confidence: 99%